2020
DOI: 10.1002/jccs.202000491
|View full text |Cite
|
Sign up to set email alerts
|

A pyrazine‐bridged trimer of oxo‐centered triruthenium–carbonyl clusters and the supramolecular assembly built from multiple noncovalent contacts

Abstract: The crystal structure of a new pyrazine-bridged trimer of oxo-centered triruthenium-carbonyl clusters formulated as [Ru 3 O(EtCOO) 6 (CO)(pyrazine)] 2 [Ru 3 O(EtCOO) 6 (CO)(μ-pyrazine) 2 ] (1) has been unequivocally determined by single-crystal X-ray diffraction (SC-XRD) analysis at 100 K. A supramolecular cyclic assembly of two trimers was formed via intermolecular COÁ Á ÁCO contacts, which is further assembled into a three-dimensional orthogonal layer-by-layer stack via hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…We use the layer-by-layer method to obtain polyruthenated porphyrin films organized in stacked structures and the LB technology to obtain films of amphiphilic and non-amphiphilic ruthenium complexes and heterostructured films combining highly ordered structures and electroactive ruthenium complexes . We note that the electrochemical response of multilayer films fabricated with the LB method was influenced by the molecule geometry and molecular packing. , Likewise, it was demonstrated that designing the interactions and components within the multilayer structures with ruthenium complexes could lead to highly organized structures with tuned properties, such as fast electronic transport within the film. , The tailored films are especially suitable for electrochemical energy conversion and storage devices since their functioning relies on processes occurring at the electrode–electrolyte interface (e.g., electron transfer across the interface). …”
Section: Introductionmentioning
confidence: 99%
“…We use the layer-by-layer method to obtain polyruthenated porphyrin films organized in stacked structures and the LB technology to obtain films of amphiphilic and non-amphiphilic ruthenium complexes and heterostructured films combining highly ordered structures and electroactive ruthenium complexes . We note that the electrochemical response of multilayer films fabricated with the LB method was influenced by the molecule geometry and molecular packing. , Likewise, it was demonstrated that designing the interactions and components within the multilayer structures with ruthenium complexes could lead to highly organized structures with tuned properties, such as fast electronic transport within the film. , The tailored films are especially suitable for electrochemical energy conversion and storage devices since their functioning relies on processes occurring at the electrode–electrolyte interface (e.g., electron transfer across the interface). …”
Section: Introductionmentioning
confidence: 99%